Influence of vegetation and soil types on the wheatbelt termite, Drepanotermes tamminensis (Hill), in the Western Australian wheatbelt - Park, H.; Majer, Jonathan; Hobbs, R. (1994)
A survey of the distribution and density of mounds of the harvester termite, Drepanotermes tamminensis (Hill), was carried out in the Durokoppin Nature Reserve, Western Australia in 1990. Vegetation and, to a lesser extent, soil type, appears to be important factors in determining density and distribution of termite mounds within the Reserve. A more detailed study of mounds in Wandoo (Eucalyptus capillosa) woodland and Casuarina (Allocasuarina campestris) shrubland indicated that the total number and size of mounds were significantly higher in the woodland than in the shrubland. The total wet weight biomass of D. tamminensis was calculated as 3.74 [grams per square metre] (37.4 kilograms per hectare]) in the woodland and 1.69 [grams per square metre] (16.9 kilograms per hectare]) in the shrubland. Thus, of the two favoured habitats, Wandoo woodland appears to be more optimal for this termite species than the Casuarina shrubland.